An outlook on commercial dairy farming in India: A review (Indian Journal of Animal Production and Management, 2024)
The most coveted title of "The largest producer of milk in the world" is persistent in the hands of India for several decades. The said title is made possible through the constant efforts made by the Government of India through the implementation of productivity enhancement and development programmes from time to time to upsurge milk production. This paradigm shift in milk production has been contributed by many factors viz., ART with semen of high yielders; awareness of farmers regarding scientific feeding and management; disease control and prevention by vaccination and shifting farmers from traditional rearing to commercial farming etc. Commercial dairy farming is entirely different from the commonly practiced farming activities followed by the villagers who rear few cows. Commercial production is an organized and well-planned venture that provides scientific inputs in breeding, housing, feeding, management, and marketing. Focus on critical analysis regarding the requirements for commercial dairy farming, constraints faced by the commercial farmers, threats and opportunities in the industry and all other relevant aspects are covered in the review for future planning by policy makers. In this review, comparison has been made between developed countries especially USA and India on the status of milch animals, livestock production management strategies adopted etc. in commercializing the dairy industry.
Keywords: Commercial dairy farming; India